Design of arbitrary optical filters in silicon-on-insulator using evanescently-coupled Bragg gratings - Pereira-Martín, Daniel; Ortega-Moñux, Alejandro; Molina-Fernández, Íñigo; Luque-González, José Manuel; Cheben, Pavel; Schmid, Jens H.; Ye, Winnie N.; Ctyroky, Jiri; Wanguemert-Pérez, Juan Gonzalo (My University, 2019)
Spectral filters are experiencing an increasing demand in several applications of the silicon- on-insulator (SOI) platform. Many works have demonstrated that arbitrary frequency responses can be synthesized by apodizing the coupling coefficient profile of an integrated Bragg grating. However, the high index contrast of the SOI platform hinders their practical implementation, due to the difficulty of achieving the precise control required in the Bragg strength. In this paper, we propose the implementation of spectral filters using an architecture based on placing loading segments within the evanescent field region of a photonic wire waveguide. The Bragg coupling coefficient can be accurately controlled by simply moving the segments away from, or closer to, the waveguide core. The layerpeeling algorithm, in conjunction with a Floquet-Bloch modal analysis, allows to determine the spatial distribution of the segments that synthesizes the desired spectrum. The proposed topology is verified by designing a filter with five arbitrary passbands.